Evaluation of the adjuvant effect of topic Bach floral in the clinical response to non-surgical periodontal treatment in patients with type 2 diabetes: pilot study (Research, Society and Development, 2023)
Objective: To evaluate the clinical response of periodontal tissues after periodontal therapy associated with the use of Bach Flower (Rock Rose gel) in participants with type 2 diabetes mellitus. Methodology: This randomized, doble-blind, split-mouth, single-center, placebo-controlled clinical trial selected 20 participants with moderate, severe, or advanced periodontitis (stage II, III, and IV). They were divided into groups, where group 1 received Floral Rock Rose gel and group 2, saline gel. All groups received conventional periodontal treatment characterized by scaling and root planing before gel application. Clinical evaluation was performed using periodontal clinical parameters: Plaque Index (PI), Gingival Index (GI), probing depth (PPD), gingival recession (GR), and Clinical Insertion Level (CAL). Biometric parameters and hematological parameters were also evaluated. All clinical and laboratory parameters were obtained at baseline and after three months. Results: There was an improvement in periodontal clinical parameters before and after treatment in both groups (P0.05). Conclusion: The periodontal treatment performed with Rock Rose adjuvant gel (Bach Flower) was safe, efficient, and promoted the improvement of periodontal clinical parameters. However, it did not show superior results to conventional periodontal therapy.